2005
DOI: 10.1111/j.1469-0691.2005.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk-factors for the acquisition of imipenem-resistant Acinetobacter baumannii in Spain: a nationwide study

Abstract: Potential risk-factors for the acquisition of imipenem-resistant Acinetobacter baumannii were investigated in a cohort study in 25 Spanish hospitals. The clonal relationship among isolates was determined by pulsed-field gel electrophoresis (PFGE). In total, A. baumannii was isolated from 203 patients, with imipenem-resistant (MIC(90) 128 mg/L) isolates being obtained from 88 patients (43%), and imipenem-susceptible isolates from 115 patients (57%). A wide clonal distribution was observed among the imipenem-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 34 publications
2
68
2
2
Order By: Relevance
“…6, [16][17][18][19][20][21] Our findings show that patients who spent 14 days or more in the ICU had over six-fold increased risk of ICU-acquired A. baumannii infections, suggesting that ICU-acquired A. baumannii infections are due to prolonged ICU stay. Moreover, the median length of ICU stay of patients who developed ICU acquired A. baumannii infection was longer than that of other patients (18 (IQR: 10-26) days vs. 3 (IQR: 1-6) days, p<0.0001) in this study, testifying that these infections were also responsible for a significantly longer ICU stay.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…6, [16][17][18][19][20][21] Our findings show that patients who spent 14 days or more in the ICU had over six-fold increased risk of ICU-acquired A. baumannii infections, suggesting that ICU-acquired A. baumannii infections are due to prolonged ICU stay. Moreover, the median length of ICU stay of patients who developed ICU acquired A. baumannii infection was longer than that of other patients (18 (IQR: 10-26) days vs. 3 (IQR: 1-6) days, p<0.0001) in this study, testifying that these infections were also responsible for a significantly longer ICU stay.…”
Section: Discussionmentioning
confidence: 75%
“…32 The independent predictors of mortality reported in previously published studies and which were not identified in our study were: length of ICU stay, duration of intubation, inappropriate use of antibiotics after diagnosis of the infection, presence of malignancy, need for mechanical ventilation, resistance to carbapenems, recent surgery, acute respiratory failure and acute renal failure. [8][9][10][11]14,16,19,23 …”
Section: 9mentioning
confidence: 99%
“…Thus, aside from the danger posed by increasingly resistant B. fragilis, the possibility exists that even respiratory organisms such as Klebsiella pneumoniae (173) and Acinetobacter baumanii (60,106,125) may acquire resistance determinants from their temporary neighbors as they pass through the gut. Equally disturbing is the recent evidence that innocuous intestinal bacteria in cattle may be reservoirs for resistance and that mobile DNA elements (e.g., plasmids) were responsible for the rapid spread of drug resistance on farms whether or not therapeutic antibiotic use was involved (234).…”
Section: Bacteroides As a Reservoir Of Resistance Determinantsmentioning
confidence: 99%
“…baumannii is usually treated with broad-spectrum antibiotics, including carbapenems. Carbapenems such as imipenem and meropenem are often the antibiotics of last resort for such infection, and resistance against them is considered an alarming situation [13,14]. Many risk factors are associated with the prevalence of A. baumannii and the development of MDR-A.…”
Section: Introductionmentioning
confidence: 99%